2019
DOI: 10.1101/gr.234021.117
|View full text |Cite
|
Sign up to set email alerts
|

The strand-biased mitochondrial DNA methylome and its regulation by DNMT3A

Abstract: How individual genes are regulated from a mitochondrial polycistronic transcript to have variable expression remains an enigma. Here, through bisulfite sequencing and strand-specific mapping, we show mitochondrial genomes in humans and other animals are strongly biased to light (L)-strand non-CpG methylation with conserved peak loci preferentially located at gene-gene boundaries, which was also independently validated by MeDIP and FspEI digestion. Such mtDNA methylation patterns are conserved across different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
99
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(111 citation statements)
references
References 41 publications
10
99
2
Order By: Relevance
“…In both groups, the L-strand presents higher and more variable methylation patterns. The strand-biased nature of mtDNA methylation has been previously described in mouse embryos and in cancer cells (Dou et al, 2019;Patil et al, 2019), and is consistent with reports examining different mtDNA loci (Bellizzi et al, 2013). However, as far as we know, it is the first time that this phenomenon is demonstrated in bovine.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In both groups, the L-strand presents higher and more variable methylation patterns. The strand-biased nature of mtDNA methylation has been previously described in mouse embryos and in cancer cells (Dou et al, 2019;Patil et al, 2019), and is consistent with reports examining different mtDNA loci (Bellizzi et al, 2013). However, as far as we know, it is the first time that this phenomenon is demonstrated in bovine.…”
Section: Discussionsupporting
confidence: 91%
“…However, the existence of an autonomous epigenetic control of mtDNA was controversial (Hong, Okitsu, Smith, & Hsieh, 2013;Patil et al, 2019). Finally, with improvements in detection techniques, recent studies proposed that similarly to nuclear DNA, mtDNA is also subjected to cytosine methylation (Dou et al, 2019;Patil et al, 2019). These studies have successfully demonstrated, in different models, the non-random patterns of cytosine methylation in mtDNA, predominantly observed in a non-CpG context (Dou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, for speci c coding genes, mtDNA methylation levels negatively correlate with mitochondrial gene transcript abundance. However, mtDNA methylation drift with decreased methylation levels at most coding gene loci was observed in brains from older humans, and mitochondrial gene expression decreased with age [13]. Our data suggested that anesthesia and surgery induced mtDNA methylation drift at coding gene loci, thereby in uencing the transcriptional levels of COX1, ND2, and ND5, which encode the subunits of cytochrome c oxidase (complex IV) and NADH dehydrogenase (complex I)…”
Section: Discussionmentioning
confidence: 70%
“…In particular mtDNA is susceptible to reactive oxygen species (ROS), which are established determinants of DNA methylation modi cation on cytosine residues [11,12]. Although not completely characterized, emerging ndings have indicated that 5-methylcytosine (5-mC) in mtDNA can be detected in approximately 2-18% of CpG and non-CpG sites using bisul te conversion and pyrosequencing, and mitochondrially targeted DNA methyltransferase 1 (DNMT1) and DNMT3A are suggested to be responsible [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation